PENGARUH PENAMBAHAN GAS O2 PADA PENGELASAN CO2 DENGAN MENGGUNAKAN ELEKTRODA INTI FLUKS DAN SOLID TERHADAP SIFAT MEKANIS DAN VISUAL BASE METAL ST42 MARINE PLAT - Budi Santosa, Ari Wibawa (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2009)
Weld CO2 is processing electric arc welding where gas carbondioksida or CO2 as component of metal fluid canopy where at welder process there will be liquefaction of metal, in order not to invite oxidation process, what causes the happening of porosity at weldment metal. Where porosity will reduce strength to draw the metal. At welder process surely happened liquefaction process of metal. Liquefaction of the metal because hot influence where temperature dissociation energy of diatomic used by electric current and oksidator attachment, to get strong weld joint is by enough temperature to liquefy metal which will be jointed, where increasingly temperature would increasingly in and the metal wide melts. If happened addition of gas O2 at welder process hence adding oxidation process meaning to increasingly temperature. In consequence is applied welding flux core electrode to lessen porosity generated by temperature. Purpose of this research to know strength value draws, bending and visual from result of weld welder CO2 with addition of gas O2 counted 0%, 5%, 10% at steel ST42 joint I plate Thick 10 mm Marine Plate with welding flux core electrode and Solid. Method used in this research is experiment method, that is experimental method directly to object. In this case steel ST42 joint I Thick plate 10 mm 24 piece weld by using gas CO2. To get research data is applied observation method by using testing machine draws and bending and test EDSA. Data which collected then is analysed the correlation. Result of research shows existence of strength difference to draw and bending and penetration depth between additions of gas O2 counted 0%, 5% and 10% with welding flux core electrode and Solid. Based on result of research suggested in doing welder kontruksi steel ST42 with Thick 10 mm joint I at weld process CO2 majoring strength to draw suggested to applies welding flux core electrode with current 230 A, while majoring strength of compress is suggested to applies electrode solid, that strength draws and compress and penetration either from result of maximum weldment.